2020
DOI: 10.23887/jeu.v8i2.28934
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Multimedia Pembelajaran Interaktif Mata Pelajaran IPA Untuk Siswa SD Kelas V

Abstract: Penelitian pengembangan ini dilaksanakan karena kurangnya pemanfaatan media digital oleh pendidik dalam melakukan proses pembelajaran sehingga peserta didik kurang tertarik dalam belajar dan menyebabkan menurunnya hasil belajar peserta didik secara signifikan. Dilaksankannya penelitian pengembangan ini yaitu bertujuan untuk mendeskripsikan rancang bangun pengembangan multimedia pembelajaran interaktif dan validitas multimedia pembelajaran interaktif. Penelitian ini merupakan penelitian pengembangan dengan mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
53

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 22 publications
1
35
0
53
Order By: Relevance
“…The selection of research that develops science learning media because it is in accordance with the characteristics of learners, in accordance with the needs of learners. Supported by research stated that science learning media byutilizing technology to the maximum can help support the learning process of students (Dwiqi et al, 2020). In line with the opinion science learning, especially in elementary school, will lead students to learn to find out for themselves the answers to questions that they find in the learning process and can be accounted for.…”
Section: Introductionmentioning
confidence: 93%
“…The selection of research that develops science learning media because it is in accordance with the characteristics of learners, in accordance with the needs of learners. Supported by research stated that science learning media byutilizing technology to the maximum can help support the learning process of students (Dwiqi et al, 2020). In line with the opinion science learning, especially in elementary school, will lead students to learn to find out for themselves the answers to questions that they find in the learning process and can be accounted for.…”
Section: Introductionmentioning
confidence: 93%
“…Then in line with the research conducted by Abduramhman, et al (2020) who obtained the results of research that Interactive Learning Multimedia can improve students' learning outcomes in Social Sciences learning so that interactive learning multimedia is feasible and effectively used in the learning process. Furthermore, in line with the research on the development of Interactive Multimedia Learning for grade V elementary students conducted by Dwiqi, et al (2020) who obtained the results of research that interactive multimedia learning is effective in improving the learning outcomes of elementary school students and worthy to be used in the learning process.…”
Section: Introductionmentioning
confidence: 54%
“…The teacher's help as a learning facilitator will help students achieve the learning objectives determined. The results showed that the use of interactive multimedia could make students feel happy and motivated in learning, so that it can increase motivation and student learning outcomes [19] [20] [21], foster motivation, interest, and good enthusiasm for learning [20] [24] [ 25] [27] [28]. In addition, interactive learning multimedia can make it easier for students to understand the concepts and learning materials [23] [27] [29] [30], so that the use of interactive learning multimedia can improve student learning outcomes more optimally.…”
Section: Resultsmentioning
confidence: 99%